(Des)enquadrando as histórias em quadrinhos: fanzines, educações e filosofias - Almeida, Charles Lima Oliveira (2021)
From an early interest I have nurtured in Comics, initially as a reader, collector and researcher, this work proposes to discuss themes that intersect education, cultures and visual expressions. Given the epistemic potential that runs through the comics, mobilizing philosophical issues in the experience with education, I synthesized a research question: What unpredictable relationships between thoughts, images, imagination are provoked in the creation, experimentation and understanding of the fanzine as an educational space/time (un) framed? In the desire to provoke an experiment with the possibility of cohabiting relationships between thoughts and images, fanzine workshops had been planned with high school students in a school located on the outskirts of Feira de Santana- BA, which became unfeasible due to the pandemic of Covid – 19. From this scenario, we proposed to be my own workshop. Bringing to the surface of the craftsmanship of fanzines thought experiments. Education takes place desecrated from institutional places, becoming a movement that suggests paths that can lead to possible paths for educational reflections and(m) philosophies. The (Polis)feria is presented as a path of study and investigation that qualifies this territory as a movement of pulsating knowledge that manifests its own meanings on the surface of fanzines. The theoretical framework includes Nietzsche, Gilles Deleuze, Félix Guattari, Silvio Gallo and authors who helped to think about the atmosphere of the (Polis)feria, space-time of resistance through which I gathered the elements that forged new subjectivations, out of frame with the comics, the philosophy and education.